(untitled) (Nigerian Journal of Technology, 2016)
Photovoltaic (PV) system performance highly depends on meteorological parameters and, to reduce frequent maintenance and avoid PV system failure, the meteorological and electrical parameters of the system need to be monitored. This paper is on the development of a simple, reliable and high precision photovoltaic monitoring system, which obtains PV system parameters (i.e. PV panel temperature, irradiance, PV battery voltage, ambient temperature and humidity and PV system load current) in real time, display and store the parameters in personal computer. The system uses electronic sensors to obtain the PV system parameters, which are then processed by a microcontroller with Arduino Board and the parameters displayed in personal computer. C language was used for the microcontroller programming. From the experimental results obtained from the work, it shows that the parameters obtained using the developed systems have good correlations with those obtained using standard commercial instruments used in meteorological stations and laboratory for measurements of the same parameters. The mean bias error of the parameters obtained using the developed system to those obtained using meteorological/laboratory instruments are 0.043%, 0.0412%,-0.297% and 0.024% for solar radiation intensity, temperature, humidity and PV battery voltage measurements respectively. The research would provide PV end-users with important information that will be useful in improving PV system performance by reducing frequency of maintenance and also avoid PV system failure. http://dx.doi.org/10.4314/njt.v35i4.27